In vitro antifungal activity of crude extracts of Piper tuberculatum - Palacios, Zahyda G.F. (2009)
Piper tuberculatum Jacq. (Piperaceae) is used in traditional Peruvian medicine as anti-inflammatory and disinfectant of wounds in humans and domestic animals. This species contains amides bearing isobutyl, pyrrolidine, dihydropyridone and piperidine moieties. The aim of this work was to investigate antifungal activity of crude extracts from the spikes, leaves and stems of wild plants extracted with CH2Cl2:MeOH (2:1), EtOH, decoction, and in vitro plants extracted with CH2Cl2:MeOH (2:1). The crude extracts showed antifungal activity on Trichophyton rubrum, Mycosporum canis y M. gypseum. The minimum inhibitory concentration (MIC) observed with CH2Cl2:MeOH (2:1), EtOH and decoctions extracts against T. rubrum, M. canis and M. gypseum was 0,1 mg/mL for spikes and leaves, and 0,1 to 0,5 mg/mL for stems. The inhibition of growth using in vitro plants on T. rubrum and M. canis was 100% in 0,5 mg/mL, and 95% on M. gypseum 95% using 1,5 mg/mL of concentration.